Oncological emergency surgery for metachronous large and small bowel metastases after pancreaticoduodenectomy for pancreatic cancer: a case report - Mamoru Miyasaka; Takehiro Noji; Kimitaka Tanaka; Yoshitsugu Nakanishi; Toshimichi Asano; Yuma Ebihara; Yo Kurashima; Toru Nakamura; Soichi Murakami; Takahiro Tsuchikawa; Keisuke Okamura; Toshiaki Shichinohe; et al. (Surgical Case Reports, 2018)
Abstract Background A surgical case of metachronous metastases of pancreatic head cancer (PC) to the large and small bowel is extremely rare. Therefore, there are only a few reports about surgery for intestinal metastases from PC. An oncologic emergency is defined as an acute, potentially life-threatening condition in a cancer patient that developed directly or indirectly because of the malignant disease or cancer treatment. Case presentation A 63-year-old man with PC underwent pancreaticoduodenectomy after receiving neoadjuvant chemotherapy with gemcitabine and S-1. Histopathologically, the tumor was diagnosed as poorly differentiated, tubular adenocarcinoma, with pT2, N0, pStage IB according to the UICC classification, seventh edition. R0 was achieved. Three months after pancreatoduodenectomy, blood tests showed coagulation derangements with high C-reactive protein (CRP 11.30 mg/dl). Computed tomography (CT) scan revealed a 55-mm mass alongside the transverse colon. During 2 weeks of follow-up, the coagulation derangement and elevated CRP persisted. Repeat CT showed that the tumor enlarged to 65 mm, and an additional mass, 25 mm in diameter, was detected in the jejunum. He was hospitalized due to abdominal pain and diarrhea with persistent high fever and was inspected; however, there was no evidence for infections. With the understanding that his life-threatening symptoms were secondary to the underlying malignancy, extirpation of the tumors combined with partial resection of the transverse colon and the jejunum was performed on the eighth day of hospitalization, on an emergency basis. The lesions were identified as large and small bowel metastases from PC because histopathological examination revealed morphological features similar to the primary disease. Immediately after the emergency surgery, the fever resolved and the CRP level normalized. He was discharged and received nab-paclitaxel with gemcitabine chemotherapy for 2 months postoperatively. He selected for best supportive care after this. The patient died due to a relapse with mesenteric lymph node metastasis 7 months after the emergency surgery. Conclusion Surgery as an oncological emergency for selected patients could sometimes contribute to improving patient’s quality of life.